Pancasila sebagai Sistem Etika - Arya Wibawa Atmanegara; Ayunda Cinta Dinanti; Utama, Muhammad Daffa Adika; Randika Aryasatya Adipermana; Salman Sahid Sabiq; Sulthan Ariq Haikal; Yayang Furi Furnamasari (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Pancasila and ethics are intertwined because they both teach positive values. Pancasila ethics are based on Pancasila values, such as divinity, humanity, unity, populism, and justice. From these values, the Pancasila ethical system emerged which serves as a guideline for individual behavior in social life in Indonesia. The Pancasila ethical system continues to be developed in its implementation, so that every step and effort of the Indonesian people in achieving common goals can be directed correctly. This research uses a qualitative approach with literature study methods or literature research. This research focuses on written works, including research results that have been published. The main source of data for this article is the results of research published through google scholar. Data collection is carried out using the keywords